ANALYSIS OF THE DISTRIBUTION OF AIR POLLUTANTS USING THE AERMET METEOROLOGICAL MODEL AND THE GAUSSIAN DISPERSION MODEL - Amran; Wahyuni; Alwi Sibali; Enni Tri Mahyuni; Firman Menne; Malik; Mohamad Ali Wardana (Adisam Publisher, 2024)
Air pollution is a condition where air quality decreases and is contaminated with substances, and if these substances are dangerous or not dangerous, they can cause human health problems. One type of pollutant that needs to be considered is air pollution due to the operation of machines. Machine operation using Palm Shells, and diesel fuel for factory operations. As a result, the operation of the engine produces several exhaust gases such as Nitrogen Dioxide (NO2), Sulfur Dioxide (SO2), Particulates (PM), and Mercury (Hg). To find out the distribution pattern of chimneys, you can use the Aermod View software, and data processing is needed on Aermap. In this study, the meteorological data analysis method was used with the data input system in the Aermod View software. The purpose of this study is the analysis of meteorological data for Aermod View software input. The data obtained is meteorological data consisting of wind direction, wind speed, reference wind height, temperature, rainfall, air humidity, surface pressure, and cloud cover. Emission dispersion model for stacks on SO2, NO2, CO, and particulate parameters. The location that has the potential to receive high concentrations of these pollutants is east to southeast from the source due to a higher elevation of up to 96 meters. The maximum concentration of SO2, NO2, C, O, and particulates is at a distance of 800 meters from the emission source to the east. The condition of the area that has the maximum concentration is dominated by agricultural areas. From the results of modeling without a controller, the maximum SO2 concentration at the receptor is 50.2 µg/m3 while the quality standard is 150/1H, the maximum NO2 concentration at the receptor is 128 µg/m3, the quality standard is 200/1H, the concentration of Carbon Monoxide (CO) is 5338 µg/m3, standard quality standard 10000/1H, The modeling results show that without using controllers, pollutant concentrations are still within the quality standards that have been set based on PP No. 22 of 2021.